Primary health care policy and vision for community pharmacy and pharmacists in Colombia (2020)
ABSTRACT: Colombia is a decentralized republic with a population of 50 million, constituted by 32 departments (territorial units) and 1,204 municipalities. The health system provides universal coverage and equal access to health care services to 95% of the population. Primary health care is seen as a practical approach that guarantees the health and well-being of whole-of-society. The National Pharmaceutical Policy (NPP, 2012) goal is "to develop strategies that enable the Colombian population equitable access to effective medicines, through quality pharmaceutical services (PS)”. There are 4,351 providers certified to deliver PS: 3,699 (85%) ambulatory and 652 (15%) hospital care. The goals for PS are: a) promoting healthy lifestyles; preventing risk factors arising from medication errors; c) promoting rational use of medicines; and d) implementing Pharmaceutical Care. There are a number of ways that ambulatory patients access medications: through intermediary private companies, public and private hospitals pharmacies, and retail establishments (drugstores and pharmacies). Intermediary private companies are similar to Pharmaceutical Benefits Management in the U.S. health system, and act as intermediaries between health insurers, pharmaceutical laboratories, and patients. Pharmacists are being employed by these companies and in health insurance companies managing, auditing and delivering rational use of medicines programs. In 2014 there were approximately 20,000 pharmacies and drugstores, (private establishments) where a significant number of prescription-only medicines are sold without medical prescription. Colombian laws allow personal without pharmacy education to be a “director” in these establishments, so the training and education of persons working in drugstores and pharmacies is an important challenge. There about 8,000 registered pharmaceutical chemists with 25% to 30% working in patient care. Since the 90´s, there are more favorable conditions for pharmacist’s participation and contribution to health system and patient’s health outcome. These environmental facilitators include: a) laws and regulations regarding pharmaceutical services (2005-2007), b) establishment of a NPP (2012), and c) opportunities associated with the consolidation of private health management companies providing health services with an interest in pharmaceutical services (since 1995). Finally, telepharmacy, comprehensive care routes for pharmaceutical services, and further strengthen of postgraduate training in pharmacy practice are future strategies to improve the pharmacy profession in Colombia. They provide an opportunity to influence the recognition and value of the pharmacist as the health care professional.